Field notes contributed by John Van Dyk, fall 1979 - Van Dyk, Johnet al (1979)
Field notes contributed by John Van Dyk, includes bird sightings, locations and weather conditions.This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1979. Epson - sheet feed/flatbed